Potential predictive marker of treatment effectiveness in patients with osteopenic syndrome after surgical menopause - Yansiiat Z. Zaydieva; Elena V. Kruchinina; Olga S. Gorenkova; Elena Yu. Polyakova; Elena N. Kareva; Daria O. Kurguzova; Natalya A. Kochina; Katherine V. Krasnoshchok; Svetlana Yu. Serebrova (IP Berlin A.V., 2020)
Introduction. Patients with surgical menopause have a risk for osteopenic syndrome (OS). Menopausal hormone therapy (MHT) in combination with calcium and vitamin D promotes increase in bone mineral density (BMD). The expression level of vitamin D receptor in mononuclear fraction cells (MNFC) of blood can be considered as a predictive marker of effectiveness of OS therapy. Aim. To search a molecular predictive marker of the effectiveness of OS treatment. Materials and methods. The study included 100 women aged 4055 years with a duration of surgical menopause from 12 months to 6 years. The criterion for including patients in the study was the absence of contraindications to the use of MHT. The subject of the study was the determination of BMD by dual-energy X-ray absorptiometry, polymerase chain reaction diagnostics of the level of expression of vitamin D genes, estradiol and progesterone receptors, determination of 25-OH vitamin D in the blood. Results. Analysis of 12-month OS therapy effectiveness evaluated with a surrogate marker BMD. The increase in BMD up to 34% per year was treated as absence of negative dynamics, more than 4% per year as positive one. Significant effect of combination therapy compared with MHT on BMD in patients with surgical menopause with a low baseline level of BMD (due to hypovitaminosis D) is associated with the anti-inflammatory, bone-protective effect of vitamin D. In both groups of patients not responding; to the prescribed therapy we were able to conduct a comparative analysis of expression level of the target molecules in the MNFC before the start of treatment. The efficacy of MHT and combination therapy for BMD disorders is positively associated with the expression level of vitamin D receptors in MNFC before treatment. Therefore, the vitDR mRNA level is a potential predictive marker of the effectiveness of OS treatment. The expression levels of nuclear estradiol beta receptor and membrane receptor for progesterone in MNFC before treatment showed an upward trend in women responding to therapy. Conclusion. The expression level of the vitamin D receptor in MNFC of blood is significantly lower in the group of women with no/insufficient effect on 12-month combined therapy. This indicator can be considered as a predictive marker of the effectiveness of OS therapy.